(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
discectomy in patients with prolapsed intervertebral disc. Methods: This descriptive study was conducted from 3rd January 2018 to 23rd January 2020 in Orthopaedics and Spine Department Khyber Teaching Hospital Peshawar. All patients with prolapsed intervertebral disc in the lumbar spine and fulfilling the inclusion criteria were operated for single level lumbar discectomy. Post operative clinical outcome at one year was assessed with Oswestry Disability Index(ODI) and Modified Stauffer-Coventry criteria. The clinical outcome through Oswestry Disability Index (ODI) was interpreted as minimal, moderate, sever, crippled and bed bound disability while results of Modified Stauffer-Coventry criteria were graded as excellent, good, fair and poor clinical outcome. The clinical outcome score among stratified patient age, gender, occupation and education level was compared and P value was calculated with Chi-square test(P < 0.05 was considered significant). Results: The total number of patients in our study were 50. The mean age was 42.6 ± 9.56 years(18-50 years). Male patients were 22(44%) and female 28(56%).Post operatively minimal disability was noted in 33(66%) patients, moderate in 9(18%) and severe in 8(16%) patients as assessed with ODI. Clinical outcome assessment with Modified Stauffer-Coventry criteria reported excellent outcome in 19(38%), good in 15(30%), fair in 12(24%) and poor in 4(8%) patients. Male patients with light physical work had better score than female patients and male patients with heavy manual work(P < 0.05). No major complication reported. Conclusion: Single level lumbar discectomy in patients with prolapsed intervertebral disc produced satisfactory outcome with minimal disability in majority of our patients.